An equation of drying kinetics for cementitious materials. Issue 12 (10th September 2018) - Zhang, Zhidong; Thiery, Mickaël; Baroghel-Bouny, Véronique
ABSTRACT: Concrete structures are often subjected to drying in the natural environment. To simulate moisture transport in concrete during drying, a continuum model is commonly used, which generally requires the measured water vapor desorption isotherm as input data to address the equilibrium between liquid phase and water vapor at a given temperature. The main problem in measuring desorption isotherms is that the sample needs very long time to reach mass equilibrium at a certain relative humidity. To improve the method of measurement of sorption isotherms, we proposed to use Weibull equation to determine the mass loss at the infinite time. However, Weibull equation does not work well with the anomalous drying kinetics that were recently reported in the literature. In this paper, based on the theory of dual-porosity, a new equation is proposed by separating the moisture transport in the large and small pores to estimate the drying kinetics for cementitious materials. Fitting the drying kinetics measured by the dynamic vapor sorption analyzer shows that the newly developed equation has a very high capability for a large range of relative humidities, especially for the anomalous drying kinetics. This paper also demonstrates that using the proposed equation can reduce the duration of measuring desorption isotherms.